2022
DOI: 10.1101/2022.01.04.22268749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated with COVID-19 Testing among People who Inject Drugs: Missed Opportunities for Reaching those Most at Risk

Abstract: People who inject drugs (PWID) are vulnerable to SARS-CoV-2 infection. We examined correlates of COVID-19 testing among PWID in the U.S.-Mexico border region and described encounters with services or venues representing potential opportunities (i.e., "touchpoints") where COVID-19 testing could have been offered. Between October, 2020 and September, 2021, participants aged ≥18 years from San Diego, California, USA and Tijuana, Baja California, Mexico who injected drugs within the last month completed surveys an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…It also appears that PWID sufficiently concerned about possible exposure to warrant diagnostic testing may be more motivated to be vaccinated. This finding was also observed in the US-Mexico border region, where a similar proportion of PWID (32%) had received diagnostic testing for SARS-CoV-2 [29] and testing was associated with higher vaccine uptake [31]. Further, in a multicity comparative study conducted in the general population in the USA, UK, and Australia, knowing someone personally who had COVID-19 was positively associated with willingness to be vaccinated [18].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It also appears that PWID sufficiently concerned about possible exposure to warrant diagnostic testing may be more motivated to be vaccinated. This finding was also observed in the US-Mexico border region, where a similar proportion of PWID (32%) had received diagnostic testing for SARS-CoV-2 [29] and testing was associated with higher vaccine uptake [31]. Further, in a multicity comparative study conducted in the general population in the USA, UK, and Australia, knowing someone personally who had COVID-19 was positively associated with willingness to be vaccinated [18].…”
Section: Discussionsupporting
confidence: 55%
“…The following variables were also hypothesised to be associated with vaccine uptake: HIV and HCV antibody serostatus [28,29], frequency of injection and drug last injected as a proxies for severity of substance use disorder and possible indicators of structural barriers to accessing health care [30], and current opioid agonist therapy (OAT) and recent (past year) imprisonment given the potential for greater access to health professionals to facilitate vaccination in these settings. A history of COVID-19 testing [31] was also included in the model, as people who had a reason to test for COVID-19 may have had more incentive and/or greater access to vaccination. Duration of vaccine eligibility was also included in the model; however, age was excluded due to confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agree with those in the literature that found COVID-19 testing was not broadly accessed by drug users and other marginalized populations [ 45 ]. However, most studies were conducted mainly in injection drug users [ 45 , 46 ], and found that less than a third had ever been tested [ 47 ]. Our study differs from this literature in that a very small proportion of our participants reported injecting drugs (1.4% of the MASH cohort).…”
Section: Discussionmentioning
confidence: 99%
“…Care is culturally and linguistically adapted, free, and accessible regardless of insurance coverage or immigration status. It was within this context that the Mexican Section of the USMBHC, with the MHU, began working closely with the CDC to reduce the impact and stop the spread of COVID-19, as well as other potential disease threats (5,6).…”
Section: Introductionmentioning
confidence: 99%